PERKEMBANGAN BENTUK DAN FUNGSI PATUNG LORO BLONYO DALAM MASYARAKAT DI SURAKARTA - Ersnathan Budi Prasetyo (Institut Seni Indonesia Surakarta, 2012)
This study focuses on the shape and function development of Loro Blonyo statue including its application to other media within Surakarta’s society. The data collection method of this research is observation, reference research and in-depth interview. This research concludes that the statue of Loro Blonyo is the symbol of couples – Male and female, its manifest is in the shape of sensible and insensible, which represent Dewi Sri and Sadana. This statue is considered sacred in Javanese mystical belief, as the figure symbol of the embryo of Javanese people. Loro Blonyo statue was marked of noble Javanese culture, so for the rural Javanese society which could not afford it, had transformed this statue into the symbol of brides in paddys (manten pari), pestle and mortar (alu-lumpang) and the sickle (ani-ani arit). The advancement in Loro Blonyo statue has experienced friction in shapes and function from scared to profane.Key words: Loro Blonyo, myth, sacred, profane.